Accuracy of impression techniques for implants. Part 1 - Influence of transfer copings surface abrasion - Assunção, Wirley Goncalves [UNESP]; Cardoso, Alessandra; Gomes, Erica Alves [UNESP]; Tabata, Lucas Fernando [UNESP]; Santos, Paulo Henrique dos [UNESP] (Wiley, 2008)
Purpose: This study evaluated the influence of surface abrasion of transfer copings to obtain a precise master cast for a partially edentulous restoration with different inclinations. Materials and Methods: Replicas (N = 30) of a metal matrix (control group) containing two implants at 90° and 65° in relation to the benchtop were obtained using a polyether impression material and three impression techniques: square impression copings splint with dental floss and autopolymerizing acrylic resin (TRS), square impression copings abraded with aluminum oxide (TA), and square impression copings abraded with aluminum oxide and adhesive-coated (TAA). The replicas obtained in type V stone were digitalized, and the images were exported to AutoCAD software to perform the readings of possible degree alterations in implant inclinations. The results were submitted to analysis of variance (ANOVA) and Tukey test (α < 0.05). Results: Comparing the techniques with regard to the 90° implant inclination, no statistical difference was observed between the three techniques and the control group. Analyzing the three techniques with regard to the 65° implant inclination, no significant difference was seen between technique TA and the control group. Conclusions: Technique TA presented more accurate master casts than TRS and TAA techniques. The angulated implant (65°) tended to generate more imprecise master casts than implants perpendicular to the surface. © 2008 by The American College of Prosthodontists.
Keywords: Dental implants; Dental impression materials; Dental impression techniques; Prosthodontics; acrylic acid resin; adhesive agent; aluminum oxide; biomedical and dental materials; calcium sulfate; resin; chemistry; comparative study; computer program; dental etching; dental impression; denture; human; image processing; impregum; materials testing; statistics; surface property; tooth implantation; tooth prosthesis; Acrylic Resins; Adhesives; Aluminum Oxide; Calcium Sulfate; Dental Abutments; Dental Etching; Dental Implants; Dental Impression Materials; Dental Impression Technique; Dental Materials; Dental Prosthesis Design; Humans; Image Processing, Computer-Assisted; Materials Testing; Resins, Synthetic; Software; Surface Properties